Dnmt3a2 in the nucleus accumbens shell is required for reinstatement of cocaine seeking - Cannella, Nazzareno; Oliveira, Ana; Hemstedt, Thekla Joana; Lissek, Thomas; Büchler, Elena; Bading, Hilmar; Spanagel, Rainer (The journal of neuroscience, 2018)
Epigenetic mechanisms have gained increasing attention as regulators of synaptic plasticity and responsiveness to drugs of abuse. In particular, it has been shown that the activity of the DNA methyltransferase 3a (Dnmt3a) mediates certain long-lasting effects of cocaine. Here we examined the role of the Dnmt isoforms, Dnmt3a1 and Dnmt3a2, within the nucleus accumbens (NAc) on transcriptional activity of immediate early genes (IEGs) and acute and long-lasting responsiveness to cocaine and cocaine conditioned cues. Using primary striatal cultures, we show that transcription of Dnmt3a2, but not that of Dnmt3a1, is activated by dopamine D1 receptor signaling and that knockdown of Dnmt3a2 using viral vector-mediated expression of Dnmt3a2-specific shRNAs impairs induction of the IEGs, Arc, FosB, and Egr2. Acute cocaine administration increases expression of Dnmt3a2 but not that of Dnmt3a1 in the NAc shell. In contrast, in the NAc core, expression of Dnmt3a1 and Dnmt3a2 was unaffected by cocaine administration. shRNA-mediated knockdown of Dnmt3a2 in vivo impairs the induction of IEGs, including Egr2 and FosB indicating that Dnmt3a2 regulates cocaine-dependent expression of plasticity genes in the rat NAc shell. Cocaine self-administration experiments in rats revealed that Dnmt3a2 regulates drug cue memories that drive reinstatement of cocaine seeking as well as incubation of this phenomenon within the NAc shell. Dnmt3a2 does not influence the primary reinforcing effects of cocaine. Thus, Dnmt3a2 mediates long-lasting cocaine cue memories within the NAc shell. Targeting Dnmt3a2 expression or function may interfere with cocaine craving and relapse. SIGNIFICANCE STATEMENT In humans, drug craving can occur in response to conditioned cues, even after extended periods of abstinence. In rats, cue-induced cocaine seeking has been shown to increase progressively during the first 2 months of abstinence from drug self-administration. This phenomenon, referred to as incubation of cocaine seeking, is consistent with the hypothesis that in humans craving increases over time and remains high following prolonged abstinence. Those long-lasting behavioral changes are likely to be mediated by epigenetic effects and neuroplastic changes within the mesolimbic brain reward system. Here we show that a specific isoform of DNA-methyltransferases in the NAc shell regulates drug cue memories that drive reinstatement of cocaine seeking after both early abstinence and incubation of cocaine craving.